Repurposing anticancer drugs for the management of COVID-19. (December 2020) - El Bairi, Khalid; Trapani, Dario; Petrillo, Angelica; Le Page, Cécile; Zbakh, Hanaa; Daniele, Bruno; Belbaraka, Rhizlane; Curigliano, Giuseppe; Afqir, Said
Abstract: Since its outbreak in the last December, coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has rapidly spread worldwide at a pandemic proportion and thus is regarded as a global public health emergency. The existing therapeutic options for COVID-19 beyond the intensive supportive care are limited, with an undefined or modest efficacy reported so far. Drug repurposing represents an enthusiastic mechanism to use approved drugs outside the scope of their original indication and accelerate the discovery of new therapeutic options. With the emergence of COVID-19, drug repurposing has been largely applied for early clinical testing. In this review, we discuss some repurposed anticancer drugs for the treatment of COVID-19, which are under investigation in clinical trials or proposed for the clinical testing. Graphical abstract: Image 1 Highlights: Drug repurposing for COVID-19 is a solution to rapidly supply the therapeutic options. Twenty potential antitumour drugs discussed in this review showed promising anti-COVID-19 efficacy. A number of these anticancer molecules are currently investigated in clinical trials.